Armando Pereira, Novela de la revolución cubana (1960-1990). UNAM, México, 1995; 292 pp. - Rodríguez-Luis, Julio (El Colegio de México, 1998)
Se reseñó el libro: Novela de la revolución cubana (1960-1990).